EFEKTIVITAS PUSAT INFORMASI KONSELING REMAJA (PIK-R); STUDI KUALITATIF DENGAN TEKNIK MOST SIGNIFICANT CHANGE (MSC): The Effectiveness of The Adolescent Counseling Information Center (Pik-R); Qualitative Study with Most Significant Change (MSC) Technique - Nugroho, Yoga Tri; Ena Sari, Rumita; Meckarische, Arnild Augina (Poltekes Kemenkes Tanjungpinang, 2021)
This study aimed to describe the most significant change stories in the indicators of the effectiveness of the Adolescent Counseling Information Center (PIK-R) at SMA Negeri 4 Kota Jambi. This research was qualitative study with a narrative approach. Data collected by FGD and indepth interview with the Most Significant Change (MSC) technique. In the effectiveness dimension, the most significant change story was the increasing in life skills of PIK-R members in organizational life. Life skills of PIK-R members was in the form of physical, mental, emotional, and spiritual skills, such as being able to solve problems well, think critically, creatively, be innovative in developing PIK-R progress and the ability to communicate better, bolder and more confident.Furthermore, this was the most significant change because PIK-R 4G SMAN 4 Jambi City has clear objectives, the right strategy and program, but the provision of facilities and infrastructure is incomplete, namely not having a room for PIK-R, the implementation of activities still relies on the supervisor. PIK-R, as well as the implementation of strategy and formulation of activity programs have not run optimally. So that, in the effectiveness dimension, the implementation of PIK-R 4G at SMAN 4 Jambi City has not been effective.